Global unique solutions for the 2-D inhomogeneous incompressible viscoelastic rate-type fluids with stress-diffusion - Xi Wang; Xueli Ke (AIMS Mathematics)
We establish the global unique solution for the 2-D inhomogeneous incompressible viscoelastic rate-type fluids with stress-diffusion by employing the standard energy method and the standard compactness arguments.